Magnetic Field Intensity Modification to Force Free Model of Magnetic Clouds: Website of Wind Examples From Launch to July of 2015 - Wu, Chin-Chun; Lepping, R. P.; Berdichevsky, D. B. (Frontiers in Physics, 2021)
We describe a new NASA Website that shows normalized magnetic field (B) magnitude profiles within Wind magnetic clouds (MCs) (i.e. observations versus basic-model versus modified-model) for 209 MCs observed from launch in late 1994 to July of 2015, where the model-modification is based on the studies of Lepping, Berdichevsky, and Wu (2017; Solar Phys., 292, 27) and Lepping et al. (2018; Solar Phys. 293: 162); the basic force free MC parameter fitting model employing Bessel function (Lepping, Jones, and Burlaga,1990; J. Geophys. Res., 95, 11,957) is called the LJB model here. The fundamental principles should be applicable to the B-data from any spacecraft at 1 AU. Earlier (in the LJB study) we justified why the field magnitude can be thought of as decoupled from the field direction within a MC, and further we justified this idea in terms of actual observations seen over a few decades with examples of MCs from Wind data. The model modification is achieved by adding a correction (“Quad”) value to the LJB model (Bessel function) value in the following manner: B(est)/B0 ≈ [LJB Model + Quad(CA,u)], where B0 is the LJB-estimated field magnitude value on the MC’s axis, CA is the relative closest approach (see Appendix A), and where u is the distance that the spacecraft travels through the MC from its entrance point. In an average sense, the Quad technique is shown to be successful for 82% of the past modeled MCs, when Quality (Q0) is good or excellent; see Appendix A. The Quad technique is successful for 78% of MCs when all cases are considered. So the Q0 of the MC LJB-fit is not a big factor when the success of the Quad scheme is considered. In addition, it is found that the Quad technique does not work better for MC events with higher solar wind speed. Yearly occurrence frequency of all MC events (N_Yearly) and those MC events with ΔσN/σN2 ≥ 0.5 (N_ΔσN/σN2 ≥ 0.5) are well correlated, but there is no solar cycle dependence for normalizing NΔσN/σN2 ≥ 0.5 with N_Yearly.